1998
DOI: 10.1097/00005373-199804000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Symptom Presentation after Electrical Injury

Abstract: The neuropsychological syndrome of electrical injury survival includes physical, cognitive, and emotional complaints. Considering that most electrically injured patients are treated within the acute medical setting, greater attention needs to be directed early in the course of treatment toward addressing neuropsychologic and psychiatric issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 20 publications
4
29
1
Order By: Relevance
“…Additionally, the patient suffered a low voltage electric injury (<1000 V) with a hand-to-foot current pathway that is theoretically remote to the region affected. This is consistent with the findings reported by Pliskin et al [11], who found no relation between the frequency of cognitive, somatic and emotional complaints and injury parameters (like voltage, loss of consciousness, etc.). Though, Cooper [13] found a correlation of various factors like type of current (AC/DC), resistance of tissues, pathway of current, duration of contact with current and environmental factors (temperature, humidity, etc.)…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, the patient suffered a low voltage electric injury (<1000 V) with a hand-to-foot current pathway that is theoretically remote to the region affected. This is consistent with the findings reported by Pliskin et al [11], who found no relation between the frequency of cognitive, somatic and emotional complaints and injury parameters (like voltage, loss of consciousness, etc.). Though, Cooper [13] found a correlation of various factors like type of current (AC/DC), resistance of tissues, pathway of current, duration of contact with current and environmental factors (temperature, humidity, etc.)…”
Section: Discussionsupporting
confidence: 93%
“…This lack of past or family history again indicates towards the authenticity of this diagnosis. The literature review also supported the conclusion, where many psychiatric manifestations have been recorded out of proportion to the severity of electrical injury as well as unrelated to the apparent pathway of current [3,11]. The next important question to be answered is; does the clinical picture represent some neurological derangement induced by electrical injury or a mere response to stress?…”
Section: Discussionmentioning
confidence: 52%
“…This employment rate is higher than those reported by other EI studies 14,21 with shorter followup intervals. One such study found that 32.5% of EI participants successfully returned to work following injury.…”
Section: Discussioncontrasting
confidence: 67%
“…The list of symptoms and diagnoses utilized in the study were developed based on extensive review of the literature [4][5][6][8][9] and review of over 50 medical and neuropsychological electrical injury case files. Each symptom was categorized as either systemic, path localized, or neuropsychological.…”
Section: Methodsmentioning
confidence: 99%
“…In DEI there exists diffuse symptomatology that has components that exist remote to the theoretical current pathway. This type of injury produces remote physical, and often neurological and/or neuropsychological symptoms that exist even in the total absence of a theoretical current path that includes the brain [4][5][6][7]. Because research in DEI has been limited somewhat by its rare occurrence, researchers have found it difficult to recruit enough DEI patients, particularly women, to a research site to participate in lab research studies.…”
Section: Introductionmentioning
confidence: 99%